Surface Remelting of Multi-Phase Sintered Steel - Agata Wronska; Agata Dudek; Jacek Selejdak (Communications - Scientific letters of the University of Zilina, 2012)
This study presents the results of the investigations of the effect of surface remelting using arc welding (GTAW) on the microstructure and selected properties of surface layer of sintered steels 304L and 434L. It was found that in order to improve surface quality in these sinters, remelting should be carried out at lower current intensities, i.e. 30A and 40A. The surface treatment carried out in the study allowed for obtaining an uniform cellular-dendritic microstructure in surface layer. X-ray examinations demonstrated the effect of compressive stress in surface layer, which reduces the risk of cracking on the surface.